Histomorphometric and histologic evaluation of the effects of leukocyte platelet-rich fibrin (L-PRF) and nano-hydroxyapatite (nHA) on bone regeneration in rabbits - Tayebeh Mobaleghi; Reza Vafadoost; Rokhsare Sadeghi; Fatemeh Mashhadi-Abbas; Hamid Ahmadian-Moghadam; Hossein Semyari; Hassan Semyari (Journal of Dental Materials and Techniques, 2023)
Introduction: The study aimed to assess the histologic and histomorphometric effects of leukocyte platelet-rich fibrin (L-PRF) and nano-hydroxyapatite (nHA) on the regeneration of calvarial bone defects in rabbits.Methods: Four defects were created in the calvaria bone of 14 New Zealand rabbits and filled with L-PRF clot, nHA, or a combination of L-PRF and nHA. The fourth defect remained unfilled to serve as the control group. The rabbits were sacrificed either at 4 or at 8 weeks, and the specimens were evaluated for the type and degree of inflammation, foreign body reaction, new bone formation, and residual biomaterial particles.Results: The histomorphometric analysis revealed that L-PRF significantly enhanced osteogenesis (P<0.05), and the number of subsequent remnant bodies in the L-PRF group was not significantly different from the control group (P>0.05). The results of the histologic analysis showed that the frequency of central bone regeneration significantly increased in prolonged periods (P<0.05). There was no significant difference in the utilized biomaterials concerning subsequent bleeding, inflammation, foreign body reaction, and lateral bone regeneration between 4 and 8 weeks of treatment (P>0.05).Conclusion: The results showed that L-PRF was a suitable option for the induction of bone regeneration with fewer remnant bodies. However, future clinical studies are required to assess the efficacy of these biomaterials in the clinical setting. (J Dent Mater Tech 2023;12(1): 43-50)